A Discrete-Time Dynamical System of Wild Mosquito Population with Allee Effects - adults, We study a discrete-time dynamical system of wild mosquito population with parameters: - the birth rate of; rate, - maximum emergence; adults, - the death rate of; state., - Allee effects. We prove that if then the mosquito population dies; if holds then extinction or survival of the mosquito population depends on their initial (Discontinuity, Nonlinearity, and Complexity, 2026)
We study a discrete-time dynamical system of wild mosquito population with parameters: β - the birth rate of adults; α - maximum emergence rate; μ>0 - the death rate of adults; γ - Allee effects. We prove that if γ≥α(β-μ)μ^2 then the mosquito population dies and if γ